INTL ASSN BLACK PROFESSIONAL FIREFIGHTER - SCHAITBERGER,HA (Tufts Archival Research Center, 2007)
Letter from Romeo O. Spaulding, President of the Association of Black Professional Firefighters to Congressman Boucher pledging support for his bill H.R. 673. Points to the fact that this bill includes the recommendations of the Interagency Committee and Technical Study Group on Cigarette and Little Cigar Fire Safety.